Systematic Literature Review (SLR): Pengaruh Kebijakan Dividen, Kebijakan Utang, dan Ukuran Perusahaan terhadap Nilai Perusahaan - Putri Dwi Yanti; Nur Mala Sari; Dien Noviany Rahmatika (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this study is to evaluate the impact of dividend policy, debt, and firm size on firm value.. This study uses the systematic literature review (SLR) method. In this process, researchers collect, read, analyze, and organize previous journals to find important topics related to company policy. They found 55 relevant journals, some of which were selected as samples for the study. In the end, the authors collected 50 journals related to the research topic. According to the study results, the use of debt strategy has no effect on firm value, instead the use of dividends affects it negatively. This study also states how the use of debt and dividends increase each other and firm size has a good influence on firm value, although debt policy is not very important independently, debt policy is also related to dividend policy and may have an effect on firm value. Many findings have been obtained from research on the relationship between firm value, debt policy, dividends, and firm size. The parties involved also gained important cognition from this research.